PENGARUH BRAND SIGNATURE TERHADAP BRAND PERFORMANCE - Yuliani Sherlyta; Selli Prisilia Putri; Lingga Yuliana (Jurnal Bina Bangsa Ekonomika, 2024)
Telkomsel is an Indonesian corporation with an enormous position in the market in the cellular telecommunications sector. The intention of this study is to examine the impact of Brand Signature on Brand Performance using a case study of the Telkomsel brand. Using quantitative tools and a descriptive approach, conduct research. Individuals who have previously used the Telkomsel brand in Jakarta were the subjects of this study. Purposive sample was utilized with the criteria of those utilizing Telkomsel providers, and the respondents in this study were Telkomsel consumers ranging in age from 15 to 55 years. Partial Least Squares is the analysis technique applied. SmartPLS 3.3.9 analysis tool was utilized. There were 89 participants in the study. The research used primary data as its source. A Likert scale with a range of 1-4 is used in this investigation. The study's findings indicate that Brand Signature has an impact on Brand Performance. The management implication of this research is that the name Telkomsel, with just one word, can convey that the company is a telecommunications provider and is well-known in Indonesia. Telkomsel suppliers who are deeply embedded in the minds of their customers can propel the company to the forefront of their thinking